7th December: 2nd Advent Mark 1:1-8 - Chapman, Mark D. 1960- (2008)
The author reflects on the Biblical passage from the Gospel of Mark 1:1-8 which speaks of John the Baptist appearing in the wilderness and proclaiming a baptism of repentance for the forgiveness of sins. He notes that the distinctions of race, class and gender were literally washed away from such baptism. He asserts that being in Christ is shocking and those who are in Christ will often appear strange and eccentric.
Keywords: Bibel; Baptism; Bible. Mark; Forgiveness of sin; Jesus Christ; JOHN, the Baptist, Saint